O arqueoespaço geográfico: análise multiescalar - Currais de Pedras - Brasil Central - Lílian Coeli Leite da Silva (2020)
This work aims to analyze the systems of objects and actions that constituted the old geographic space in the karst region of Currais de Pedras, context of the upper-middle São Francisco River in Central Brazil. A set of multiscale geographical and geoarchaeological analyzes were carried out in different stages. The first stage consisted of a theoretical outline of the landscape from the perspective of the soil, rocks, relief, and sediments time. From a physical point of view, the regional geological-geomorphological organization remains the same with little or no modification considering when the ancient human groups inhabited that landscape and transformed it into an archeoterritory. The second stage consisted of practical application of the precepts referring to the regional geological-geomorphological organization to the identification of possible organization logics in the archeoterritory according to the opportunities there, which are accessibility, mobility, annual sunshine, topographic visual basins, potential for fixation associated with the practice of horticulture and potential in terms of hunting, fishing and foraging. This analysis was initiated in a megageomorphological approach of the central-northwest portion of Minas Gerais state, followed by the mapping and identification of the morphological units and landscape subunits of the Riacho Fundo watershed. A global analysis of the landscape subunits and the organicity between them make possible the definition of the Zones in this archeoterritory. In the third stage, the results of the analysis of the archaeological ceramics sherds and rock art were presented, here considered as geographic archaeobjects. The archeomaterials that make up the ceramic remains and the cave paintings were analyzed from an experimental and compared micromorphological approach to geomaterials, essentially physical, sampled in the study area. Preliminary matches were identified between the geomaterials and the archeomaterials, which subsidized the tracing of the movements carried out by the old human groups in this archeoterritory. In the fourth and last stage, a theoretical model was presented based on the inflection of the concept of geographic space traditionally applied to hodiernal. In this model, the superimposition and taphonomization of geographic archaeospaces are considered. Finally, all the results prove that understanding a past action performed in a geographic archeospace, however complex and incomplete it may be, can be accomplished by essentially geographic and geoarchaeological analysis. A preliminary organization of possible geographic archeospaces in the karst region of Currais de Pedras is proposed, considering that how older system of objects and actions are, more complex and incomplete their understanding tends to be.